Penggunaan Sosial Media Sebagai Konten Marketing Dalam Strategi Pemasaran Di Glasmacher Coffee: Social Media Applications as Marketing Content in Marketing Strategy at Glasmacher Coffee - Rosandi Ardi Noegraha; Latif Bisri; Abdul Malik Karim Amarullah Lestaluhu (Jurnal Bisnis dan Ekonomi, 2025)
AbstractThis study aims to analyze the use of Instagram as marketing content within Glasmacher Coffee's marketing strategy. The background to this research is based on the increasing use of social media in Indonesia, particularly Instagram, which has become a primary means of marketing products and services, including the coffee shop industry. Initial observations indicate that Glasmacher Coffee utilizes its official Instagram account, @glasmacher.coffee, as a promotional medium through uploading photos, videos, reels, and stories to increase brand awareness and attract new customers. The research method used was descriptive qualitative, with data collection techniques including in-depth interviews, direct observation, open-ended questionnaires, and documentation. Data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that Glasmacher Coffee's Instagram marketing strategy focuses on creating aesthetically pleasing visual content relevant to its target audience of young people. The use of Instagram features such as feeds, reels, and stories has proven effective in increasing consumer engagement. However, this study also identified challenges such as limited human resources, changes in the Instagram algorithm, and a lack of consistency in content management. The study concluded that using Instagram as a content marketing medium can increase brand awareness and build engagement with consumers, although more consistent content management and strategies that adapt to changing digital trends are still needed. Keywords: Social Media, Instagram Marketing, Content Marketing, Coffee Shop, Digital Marketing